Pop goes the weasel - Patterson, James, 1947- (New York : Warner Books, 2000)
A serial killer unleashes a reign of terror in Washington against black women. Detective Alex Cross goes after him and discovers a British embassy official who masquerades as a black taxi driver to lure his victims.
Reprint. Oiginally published: Boston : Little, Brown and Co., c1999.
"Warner Vision Books."
Accelerated Reader AR
Keywords: Cross, Alex (Fictitious character) -- Washington (D.C.) -- Fiction; Psychologists -- Washington (D.C.) -- Fiction; Serial murders -- Washington (D.C.) -- Fiction; Diplomatic and consular service, British -- Washington (D.C.) -- Fiction; Taxicab drivers -- Washington (D.C.) -- Fiction; Psychopaths -- Washington (D.C.) -- Fiction; Trials (Murder) -- Washington (D.C.) -- Fiction; Mystery fiction